2002
DOI: 10.1063/1.1513659
|View full text |Cite
|
Sign up to set email alerts
|

Local structure and luminescence of nanocrystalline Y2O3:Eu

Abstract: Nanosized Y2O3:Eu was synthesized by using a solution–combustion method. The samples were characterized by x-ray diffraction, extended x-ray absorption fine structure (EXAFS), and photoluminescence spectroscopy. Our EXAFS result showed that the local environments surrounding both Y and Eu atoms had obviously changed when the particle size was smaller than 10 nm. The coordination number and the bond length of Y (Eu)–O shell increased and the disorder became larger. This change also produced an emission peak and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 12 publications
6
83
0
Order By: Relevance
“…This makes it a versatile tool to study persistent luminescent materials since the dopant concentration will usually be very low. [18][19][20][21][22][23][24][25][26][27][28] …”
Section: Introductionmentioning
confidence: 99%
“…This makes it a versatile tool to study persistent luminescent materials since the dopant concentration will usually be very low. [18][19][20][21][22][23][24][25][26][27][28] …”
Section: Introductionmentioning
confidence: 99%
“…This differed from the normal case in which the CT band shifts when the sample dimensions change. [26,27] No excitonic band below 220 nm was observed. In the emission spectra, the peaks at 587 nm, 615 nm, and 629 nm, respectively, belong to 5 D 0 -7 F j (j¼ 1, 2) transitions of Eu 3 þ ions.…”
Section: Resultsmentioning
confidence: 92%
“…Qin et al reported enhancement of ultraviolet UC in Yb 3+ and Tm 3+ codoped fluoride film due to the decrease of Judd-Ofelt parameter X 2 , which is related to the symmetry of the ligand field [8]. Qi et al indicated that the change of local structure around the active ions lead to new emission peaks and the red shift of the charge-transfer band of the Eu 3+ ions [9]. Patra et al investigated the effect of crystal size and crystal phase on UC luminescence in ZrO 2 : Er 3+ nanocrystals [10].…”
Section: Introductionmentioning
confidence: 98%